2019
DOI: 10.1140/epjc/s10052-019-6862-9
|View full text |Cite
|
Sign up to set email alerts
|

A spherically symmetric model of anisotropic fluid for strange quark spheres

Abstract: In the present work, we try to find a solution without singularity of Einstein's field equations for the spherically symmetric perfect fluid objects, accurately strange quark spheres, taking into consideration Schwarzschild metric as the outside space-time. An ensemble of inside solutions found on the basis of the simplest linear state equation in the specific form p r = αρ − β. The energy density ρ(r), the radial pressure p r (r) and the tangential pressure p t (r) are devoid of any singularity and exhibit a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The main objective of this examination are compact spherical objects, for instance, white dwarfs and neutron stars, which depict the end-state of astrophysical progress of main-sequence stars, yet in addition other kinds of stars, for instance, brown and red dwarfs. Besides, along the decades other astrophysical objects have showed in the literature, for instance, hyperon stars [74], quark/hybrid stars [75,76], strange stars [77][78][79][80][81][82][83][84][85][86][87][88][89][90], and significantly more exotic spheres such as boson stars [91].…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this examination are compact spherical objects, for instance, white dwarfs and neutron stars, which depict the end-state of astrophysical progress of main-sequence stars, yet in addition other kinds of stars, for instance, brown and red dwarfs. Besides, along the decades other astrophysical objects have showed in the literature, for instance, hyperon stars [74], quark/hybrid stars [75,76], strange stars [77][78][79][80][81][82][83][84][85][86][87][88][89][90], and significantly more exotic spheres such as boson stars [91].…”
Section: Introductionmentioning
confidence: 99%
“…One may say that then the metric "admits" a perfect fluid as a source. Models with EOS also lead to such relations, see Eqs (31,32,33). Two similar examples are discussed in the next two sections.…”
Section: It Turns Into a Linear Equation Formentioning
confidence: 90%
“…In the literature y is given and a 1 is found from Eq (32) [30], [31], [32], [33], [34], [35], [36], [37], [38], [39]. Due to Eqs (6, 7) one finds quickly y form µ or m. Solutions with LEOS and known µ are given in [40], [41], [42] and [43].…”
Section: Types Of Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has as of late demonstrated that the ideal would be to generalize the gravastar picture by corresponding an inside solution matching to a EoS of DE to an outside solution of Schwarzschild at an interface of the junction. Such a spherically symmetrical model ought not to have a horizon and it should deal with a solution of static equilibrium, at some point alluded as a DE object [48,50,[70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%